A model NOT to be imitated?: Recent criticisms of Paul - Strijdom, Johan ca. 21. Jh. (HTS teologiese studies, 2001)
In this article recent criticisms of Paul are summarised under the headings of ethnicity (Mack), social class (Theissen), gender (Wire) and homoeroticism (Nissinen). Horsley's positive appraisal of Paul's anti-imperial stance is also surveyed. These views are introduced by means of the concept of imitation as a category of social ethics in Paul, the article, concludes with a statement on the morality of reading.